Cell membrane damage is involved in the impaired survival of bone marrow stem cells by oxidized low‐density lipoprotein. Issue 12 (25th September 2014) - Li, Xin; Xiao, Yuan; Cui, Yuqi; Tan, Tao; Narasimhulu, Chandrakala A.; Hao, Hong; Liu, Lingjuan; Zhang, Jia; He, Guanglong; Verfaillie, Catherine M.; Lei, Minxiang; Parthasarathy, Sampath; et al.
Abstract Cell therapy with bone marrow stem cells (BMSCs) remains a viable option for tissue repair and regeneration. A major challenge for cell therapy is the limited cell survival after implantation. This study was to investigate the effect of oxidized low‐density lipoprotein (ox‐LDL, naturally present in human blood) on BMSC injury and the effect of MG53, a tissue repair protein, for the improvement of stem cell survival. Rat bone marrow multipotent adult progenitor cells (MAPCs) were treated with ox‐LDL, which caused significant cell death as reflected by the increased LDH release to the media. Exposure of MAPCs to ox‐LDL led to entry of fluorescent dye FM1‐43 measured under confocal microscope, suggesting damage to the plasma membrane. Ox‐LDL also generated reactive oxygen species (ROS) as measured with electron paramagnetic resonance spectroscopy. While antioxidant N‐acetylcysteine completely blocked ROS production from ox‐LDL, it failed to prevent ox‐LDL‐induced cell death. When MAPCs were treated with the recombinant human MG53 protein (rhMG53) ox‐LDL induced LDH release and FM1‐43 dye entry were significantly reduced. In the presence of rhMG53, the MAPCs showed enhanced cell survival and proliferation. Our data suggest that membrane damage induced by ox‐LDL contributed to the impaired survival of MAPCs. rhMG53 treatment protected MAPCs against membrane damage and enhanced their survival which might represent a novel means for improving efficacy for stem cell‐based therapy for treatment of diseases, especially in setting of hyperlipidemia.